PENGARUH EKUITAS MEREK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR HONDA ADV 150 ABS (STUDI KASUS PADA KONSUMEN PT.INDOSTAR SUKSES MANDIRI MEDAN) - Jesica Jesica; Mery Lani Purba (UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
This study aims to determine the effect of brand equity and price on purchasing decisions for Honda ADV 150 ABS motorcycle PT. Indostar Sukses Mandiri Medan. The formulation of the problem in the study is how the influence of brand equity and price on the purchase decision of a Honda ADV 150 ABS motorcycle at PT. Indostar Sukses Mandiri Medan where this research uses descriptive analysis methods and statistical methods. The data used in this study are primary data and secondary data. The population in this study were customers at PT. Indostar Sukses Mandiri Medan. The results of the research based on the partial t-test for the effect of brand equity on purchasing decisions are shown by t count - 1,101 and t table of 1,688, while the effect of price on purchasing decisions is shown by t count 12,042 and t table of 1,688. By comparing F count amounting to 122.923 with F table = 3.14 means that the effectiveness of brand equity and price has a significant effect on purchasing decisions. The coefficient of determination (R2) shows that PT. Indostar Sukses Mandiri Medan that the coefficient of determination (R²) is 0.793. This means that 79.3% of purchasing decisions can be explained by brand equity and price variables, while the remaining 20.7% of decisions are influenced by other variables outside of this study, for example location, loyaltyetc.